Astylus atromaculatus (pollen beetle) gastrointestinal disease experimentally reproduced in sheep - García y Santos, Carmen (2025)
Intoxication of sheep and cattle by Astylus atromaculatus recently occurred in Uruguay and Argentina in association with severe drought. Although the disease was experimentally reproduced in sheep in the 1970s, there is limited information on clinical and pathologic findings of sheep experimentally intoxicated by this beetle. Here, we described the clinical, gross, and microscopic findings in 3 sheep orally dosed with A. atromaculatus (treatment group, TG) and in 2 control sheep (control group, CG) dosed with distilled water. Anorexia, lethargy, ruminal stasis, reluctance to move, prolonged recumbency, and bruxism were observed in the TG but not the CG sheep. Gross postmortem lesions were only observed in TG sheep and included fibrinonecrotizing enteritis affecting the duodenum, jejunum, and ileum, and multifocal hemorrhages in rumen, omasum, and abomasum. Microscopically, all 3 TG animals had multifocal necrosis in the small intestine; the lesions were most severe in the jejunum. Multifocal necrosis was seen in the mucosa of the rumen, omasum, and abomasum. No significant gross or microscopic abnormalities were observed in the 2 CG sheep. The study supports the role of A. atromaculatus in acute, fatal gastrointestinal disease like that previously described in experimental and spontaneous cases in sheep.